MINdI: Mindfulness Instruction for New Interns - Cheston, Christine C. (MedEdPORTAL, 2020)
INTRODUCTION: Trainee burnout has reached epidemic proportions and is increasing among physicians compared to non-health care professionals. Burnout is associated with depression and lower empathy, poor patient adherence to medical plans, and early physician retirement. Mindfulness is the quality of being nonjudgmental and present and has been shown to decrease physician burnout. Implementation of mindfulness curricula may decrease trainee burnout. METHODS: Using Kern's six-step approach, we developed an easy-to-implement, facilitator-friendly mindfulness curriculum for pediatric interns. Curricular sessions were held monthly during preexisting 1-hour didactics over 6 months, facilitated by individuals without mindfulness experience. Learners were assessed on knowledge, attitudes, and behavior with postintervention surveys during a pilot in 2016. Qualitative data were used for curricular improvement resulting in the published curriculum. RESULTS: Postcurriculum surveys from our pilot revealed that 69% of interns reported a more positive attitude toward mindfulness, while 62% reported having (1) greater knowledge about evidence supporting mindfulness, (2) improved knowledge on how to apply mindfulness techniques, and (3) the belief that techniques they had learned positively impacted their lives. Thirty-three percent endorsed using mindfulness techniques more frequently than they had prior to the start of the mindfulness curriculum. DISCUSSION: Our novel curriculum provided longitudinal mindfulness training that meaningfully impacted trainee knowledge, behaviors, and attitudes. The curricular structure overcame the need for local topic experts and was feasible to implement within the confines of our complex program structure. Ongoing work will determine the impact of our curriculum on objective measures of burnout, empathy, and mindfulness.